2021
DOI: 10.1182/blood.2020006020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Longitudinal Pain Study in Sickle Cell Disease (ELIPSIS) by patient-reported outcomes, actigraphy, and biomarkers

Abstract: Clinical trials in sickle cell disease (SCD) often focus on health care utilization for painful vaso-occlusive crises (VOC). However, no objective, quantifiable pain biomarkers exist, pain is not specific to VOCs, health care utilization varies between patients, unreported at-home VOCs likely contribute to long-term outcomes, and patient-reported outcomes are seldom considered. This non-interventional, longitudinal, 6-month study aimed to develop tools to identify VOCs in SCD patients with or without health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Among those studies in this SLR that included self-reported VOCs or those managed in a home setting, the mean annualized frequency was generally higher, ranging from 5.2 to 13.6 VOCs/year [ 19 – 21 ]. This is also consistent with a recent prospective cohort study published after the search period for this SLR, in which 35 U.S. patients were followed for 6 months and reported a median annualized frequency of 8 VOCs/year, with a mean duration of 2.7 days and 62.3% of VOC events self-managed at home [ 50 ]. Patients self-reported VOCs in their daily pain diary that were managed at home, in a clinic, in the emergency department, or in the hospital.…”
Section: Discussionsupporting
confidence: 90%
“…Among those studies in this SLR that included self-reported VOCs or those managed in a home setting, the mean annualized frequency was generally higher, ranging from 5.2 to 13.6 VOCs/year [ 19 – 21 ]. This is also consistent with a recent prospective cohort study published after the search period for this SLR, in which 35 U.S. patients were followed for 6 months and reported a median annualized frequency of 8 VOCs/year, with a mean duration of 2.7 days and 62.3% of VOC events self-managed at home [ 50 ]. Patients self-reported VOCs in their daily pain diary that were managed at home, in a clinic, in the emergency department, or in the hospital.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, at-home vaso-occlusive crises are underreported. The Evaluation of Longitudinal Pain Study in Sickle Cell Disease (ELIPSIS) trial has recently shown the feasibility of accurately monitoring out-of-hospital pain by using patient-reported vaso-occlusive crisis days as potential endpoints for clinical trials in SCD ( 42 ). The utilization of the quantifiable biomarker in future trials has the potential to improve this bias.…”
Section: Discussionmentioning
confidence: 99%
“…VOC samples were collected within 24 h from report. This protocol was approved by the Wayne State University Human Investigation Committee Institutional Review Board and written informed consent was obtained from study participants, previously defined in detail 10 . Participants who were being treated with HU must have been on a stable dose for at least eight weeks prior to visit 1.…”
Section: Methodsmentioning
confidence: 99%
“…More than 100 biomarkers have been identified in SCD although none have been shown to reliably predict VOCs 1‐10 . Pathologic adhesive interactions of sickle erythrocytes (SSRBCs) to the vascular endothelium contribute to VOCs, resulting in impaired microvascular blood flow, tissue ischaemia, severe pain, and end‐organ damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation